PARADIGMA MODERN DALAM RANA PENDIDIKAN ISLAM - Firdaus Firdaus (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2015)
In an effort to reform Islamic education need to be formulated clearly the implications of the verses of the Qur'an and hadith concerning the "nature" or innate potential, the mission and goal of human life. Because these formulations will be basic concepts of Islamic education philosophy. To that end, philosophy or any basic assumption of Islamic education can only be applied properly if the environmental conditions (socio-cultural) considered. So, if we want to make changes Islamic education, the first step that must be done is to formulate the basic concepts of philosophical education (a) in accordance with the teachings of Islam, (b) develop empris the principles underlying its appropriateness in the context of the environment (socio-cultural) which in this case is a civil society. Because without the basic framework of philosophical and theoretical Kuta then change Islamic education does not have a strong foundation and also do not have a definite direction. The basic concept of theoretical philosophy and Islamic education, should be placed in the context of civil society supra system in which education will be implemented.